Focus on Human Biology - Carl E Rischer (Harper Collins, 1995)
The "Focus on Human Biology" includes the basic principles of science, biology, cell biology, molecular biology, genetics, human anatomy and physiology, human evolution, and the human impact on the environment. There is special emphasis on basic human anatomy and physiology and on disease and on immunity